2012
DOI: 10.1186/1475-2840-11-64
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exenatide vs. Metformin on endothelial function in obese patients with pre-diabetes: a randomized trial

Abstract: BackgroundGlucagon like peptide-1 (GLP-1) receptor agonist treatment may improve endothelial function via direct and indirect mechanisms. We compared the acute and chronic effects of the GLP-1 receptor agonist exenatide vs. metformin on endothelial function in patients with obesity and pre-diabetes.MethodsWe performed a randomized, open-label, clinical trial in 50 non-diabetic individuals (mean age 58.5 ± 10.0; 38 females) with abdominal obesity and either impaired fasting glucose, elevated HbA1c, or impaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
84
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 33 publications
6
84
0
Order By: Relevance
“…Publication years were between 2010 and 2014, and the duration of the studies ranged from 8 weeks to 52 weeks. 2 trials compared GLP-1 agonist (exenatide) with metformin on non-diabetic individuals with abdominal obesity and either IFG, elevated HbA1c or IGT [21] and withT2DM and concomitant non-alcoholic fatty liver disease (NAFLD) [22], respectively. One trial compared GLP-1 agonist (exenatide) with placebo on a background of basal insulin with oral anti-diabetic drugs [23].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Publication years were between 2010 and 2014, and the duration of the studies ranged from 8 weeks to 52 weeks. 2 trials compared GLP-1 agonist (exenatide) with metformin on non-diabetic individuals with abdominal obesity and either IFG, elevated HbA1c or IGT [21] and withT2DM and concomitant non-alcoholic fatty liver disease (NAFLD) [22], respectively. One trial compared GLP-1 agonist (exenatide) with placebo on a background of basal insulin with oral anti-diabetic drugs [23].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The number of participants included in studies ranged from 20 [26] to 117 [22]. The range of age participants was from 18 years [24] to 69 years [21]. Moreover, each of these studies had its own inclusion criteria which are listed in Table 1.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Both studies suggested an additional cardiovascular benefit of this agent beyond the improved glycemic control in this population [76,77] . Another randomized 3-wk head-to-head study examined the effects of exenatide vs metformin on microvascular endothelial function in 50 individuals with abdominal obesity and prediabetes [78] . Similar effects of both agents were shown on microvascular endothelial function, vascular activation, oxidative stress and markers inflammation.…”
Section: Exenatidementioning
confidence: 99%
“…Exenatide did not demonstrate any beneficial effect on postprandial function in individuals with IGT. It was suggested that the reason for this observation was the administration of a glucose-only meal instead of a high fat meal, which would be expected to increase postprandial triglycerides [76,78] .…”
Section: Exenatidementioning
confidence: 99%
“…In a 16-week study of 20 patients with T2D, exenatide improved brachial artery flow-mediated dilation compared with glimepiride (8). In contrast, exenatide therapy for 3 months did not increase vasoreactivity by digital plethysmography compared with metformin in 50 obese, glucose-intolerant patients (9). Similarly, in a separate study involving 49 T2D participants, liraglutide did not improve forearm blood flow measured by venous occlusion plethysmography in response to graded infusions of acetylcholine or sodium nitroprusside relative to placebo or glimepiride (10).…”
mentioning
confidence: 96%